Long-term effectiveness of Tension-Free Vaginal Tape (TVT) procedure – twelve years after surgery - Broś-Konopielko, Magdalena; Chmielewski, Grzegorz; Jodzis, Agnieszka; Teliga-Czajkowska, Justyna; Czajkowski, Krzysztof (Family Medicine & Primary Care Review, 2017)
Background . Urinary incontinence is defined as any involuntary loss of urine. The TVT (Tension-Free Vaginal Tape) operation is a treatment for stress urinary incontinence introduced in Poland in the year 2000. There are few studies evaluating the long-term effectiveness of TVT in Polish women. Objectives . To evaluate the long-term effectiveness of TVT in the treatment of stress urinary incontinence in women. Material and methods . 40 women operated on in the period 1999–2004 were recalled 12.6 ± 1.2 years after TVT for a follow-up study. 85 vs 15% of women were operated on due to primary vs recurrent stress incontinence, respectively. 20 vs 80% of the patients had mixed vs pure stress urinary incontinence, respectively. The effectiveness of TVT operations was assessed objectively on the basis of a cough test, and subjectively on improvement after treatment according to the patientsʼ answers (yes/no), PGI -I, PS Q and VAS („0“ was the total absence of improvement after surgery, „100“ – total improvement). Results . The cough test was negative in 85% of cases. Subjectively, 85% of women declared improvement after TVT. Based on PGI -I – 77.5% of them maintained improvement after surgery. Based on PS Q – 70% of the women assessed control of urinary incontinence after surgery as better, 72.5% were satisfied with the results of the operation, and 77.5% of them would recommend TVT to other women. Based on VAS , total improvement was noted by 12.5% of women, 60% of women rated improvement “50–99”, and total lack of improvement was noted by 20% of the women. Conclusions . TVT seems to be an effective form of treatment for urinary incontinence in women 12 years after surgery.